Meaning of indices of nitric oxide system for early period of peptic ulcer disease formation in the presence of pneumonia - Furdychko, L. O.; Pohoretska, Ya. O. (Journal of Education, Health and Sport, 2018)
The diseases most often occurring in clinical picture – pneumonia and peptic ulcer disease (PUD) – have been selected for experimental investigation. The aim of the research: to determine the number of nitric oxide system indices in early period of peptic ulcer disease and experimental pneumonia (EP). Methods of investigation. The research was conducted on 35 male guinea pigs, weighing 180-210 g. Experimental pneumonia was provoked by V.N. Shlyapnikov, T.L. Solodov [et.al.] method, peptic ulcer disease was modeled by V.I. Komarov method. Activity of NO synthases was detected by V.V. Sumbaev method, L-arginine content in blood serum – by T.L. Aleinikov method, stable NO metabolites – by H.H.W. Schmidt method. Decapitation of animals was performed under ether anesthesia on the 4th and 8th days of inflammatory process formation in the lungs and gastric ulcer disease. Obtained results. Investigation of the amount of stable NO metabolites in the blood of animals with PUD and EP found that this index increased by 53.9% (P˂0.05) in relation to control animals on the 4th day of experiment. Further investigation of NO level, on the 8th day of these disease models, showed its significant increase as compared with intact animals – by 68,7 % (P˂0.05). The next index taken into account was inducible NOS (iNOS), concentration of which in the blood increased by 64,0 % (P˂0.05) on the 4th day as compared to control animals, and further this index reached its highest level – 93,4 % (P˂0.05). Activity of cNOS increased on the 4th and 8th days by 21,5 % (P˂0.05) and 28.9 % (P˂0.05), respectively, in comparison with control. Amount of L-arginine in early period decreased by 74,9 % on the 4th day, and decreased by 86,5 % on the 8th day in relation to intact animals. Conclusion. Determination of certain indices of nitric oxide system showed an increase in iNOS and cNOS and stable metabolites on the background of decrease in L-arginine amount.